2010
DOI: 10.1212/wnl.0b013e3181f25b35
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the human pedunculopontine nucleus region in voluntary movements

Abstract: Objective:The pedunculopontine nucleus region (PPNR) is being investigated as a target for deep brain stimulation (DBS) in Parkinson disease (PD), particularly for gait and postural impairment. A greater understanding of how PPNR activities and oscillations are modulated with voluntary movements is crucial to the development of neuromodulation strategies. Methods:We studied 7 patients with PD who underwent DBS electrode implantations in the PPNR. PPNR local field potential and EEG were recorded while patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 42 publications
6
60
0
Order By: Relevance
“…Local field potential (LFP) recordings from the PPN have reported oscillations in both the alpha (6-12Hz) and beta (12-30Hz) frequency bands 33,[35][36][37] , with relatively higher alpha power in caudal-PPN, and higher beta power in the rostral-PPN 35 . Active gait is accompanied by increased LFP alpha power in the caudal PPN 35 .…”
Section: Phase Locking In the Ppn Is State Dependentmentioning
confidence: 99%
“…Local field potential (LFP) recordings from the PPN have reported oscillations in both the alpha (6-12Hz) and beta (12-30Hz) frequency bands 33,[35][36][37] , with relatively higher alpha power in caudal-PPN, and higher beta power in the rostral-PPN 35 . Active gait is accompanied by increased LFP alpha power in the caudal PPN 35 .…”
Section: Phase Locking In the Ppn Is State Dependentmentioning
confidence: 99%
“…Neuronal firing did not show these oscillations, rather there pattern was bursty or regular. More recently, Tsang et al [213] showed beta synchronization in pre-movement activity in the on medication state, but not in the off medication.…”
Section: Discussionmentioning
confidence: 99%
“…of the pedunculopontine alpha-band power was observed in parallel to freezing of gait (Thevathasan et al, 2012) and coherence modulation between the pedunculopontine nucleus and cortex in the alpha band was identified in phasic wrist movement (Tsang et al, 2010). Whether alpha rhythm modulation might constitute a 'binding mechanism' to balance the contribution of cortico-spinal and nigro-ponto-reticular transmission to the spinal motor neuron might be addressed in future with combined electrophysiological recordings from the midbrain and brainstem nuclei together with MEG/EEG and EMG.…”
Section: Is Transient Suppression Of Cortical Motor Processing a Mechmentioning
confidence: 95%